The Role of Cloud and AI Technology in Providing Secure and Fast Payments - Swamy, Mamatha Adinarayana (IPHO-Journal of Advance Research in Science And Engineering, 2025)
The financial landscape has undergone unprecedented change through incorporation of cloud computing and artificial intelligence technologies, radically transforming transactional processes and payment ecosystems globally. Payment systems in emerging economies exhibit outstanding growth patterns, with the uptake of mobile payment going exponential as the constraints of conventional banking infrastructure fuel innovation in finance technology solutions. Cloud infrastructure makes it possible for payment platforms to attain higher scalability features by means of elastic resource provisioning, distributed computing models, and event-driven processing systems that can support huge transaction volumes with sub-second response times. Artificial intelligence optimizes payment security by means of advanced fraud detection algorithms that employ supervised machine learning methods, ensemble learning methods, and behavioral analysis systems with the ability to scan millions of transaction records to detect fraudulent patterns accurately. Biometric authentication solutions utilize hybrid deep learning techniques integrating convolutional and recurrent neural networks to ensure secure user authentication through fingerprint recognition, face detection, and multi-modal biometric processing. Centralized payment interfaces utilize event-driven, scalable architectures and AI-driven cache management systems to enhance API performance and support multiple payment schemes through unified interfaces. Blockchain technology is a paradigm change towards decentralized payment processing using distributed ledger systems, smart contracts, and consensus algorithms augmented by machine learning models. Patterns of cryptocurrency adoption show very strong correlations with the level of economic development, providing new notions of financial sovereignty while tackling challenges of financial inclusion in countries with low banking infrastructure levels. The intersection of cloud computing and artificial intelligence forms holistic payment ecosystems that provide better security, faster transactions, lower operational costs, and greater financial access to previously excluded populations around the world.